Experimental study on silty sand contains environmental and friendly construction materials and long-term and short-term Behavior: Micro and macro study - Mahmoud Ghazavi; Mobina Taslimi Paein Afrakoti (Results in Engineering)
Construction on silty sand soils on the riverbank, which are typically loose, can cause geotechnical problems. Therefore, it is essential to improve their short-term and long-term behavior. Sustainable development encourages geotechnical engineers to use eco-friendly materials in soil improvement. This study investigates the effect of Kenaf fibers (KF) and Persian gum (PG) biopolymer on stabilizing silty sand with low shear strength. Short-term behavior was assessed using standard Proctor compaction, unconfined compressive strength (UCS), and indirect tensile strength (ITS) tests, while long-term performance was evaluated through the direct shear test. The effects of initial moisture content, PG and KF percentages, curing time, and temperature on mechanical properties were analyzed. Additionally, ultrasonic pulse velocity (UPV) and scanning electron microscopy (SEM) tests examined the microstructure of the improved soil. Results showed that the optimum PG and KF contents were 2.5 % and 1 % by soil weight, respectively. The UCS of samples containing these additives increased by 75 % compared to unstabilized soil. The highest UCS was achieved at 50 °C, with 5.1 times increase, while at 110 °C, it decreased by 67 % due to thermal degradation. Direct shear tests confirmed that KF reinforcement consistently improved shear strength. The UPV showed a strong correlation with UCS, supporting its use as a non-destructive evaluation method. Also, SEM analysis showed that PG enhanced particle bonding, while KF reinforcement created a denser and more interconnected soil structure. This study highlights the effectiveness of PG and KF as sustainable alternatives for soil stabilization, showing improved soil properties and environmental issues.